Crisis management the overlooked implications of Section 17, Article XII (2020)
During emergencies, Congress may empower the President to take over public utilities and private businesses to serve the public interest. Jurisprudence characterizes this power of the State as an exercise of police power, for which no just compensation is due to the persons affected by the taking. This Article proposes that the takeover clause under Section 17, Article XII of the 1987 Constitution may also be characterized as an exercise of the power of eminent domain, which would entitle affected entities to secure just compensation. This recharacterization has implications on the arguments and defenses, as well as the fact and basis of just compensation, and the manner of determining the amount due. Any challenge to the exercise of the State's power under Section 17, Article XII must keep these considerations in mind.
Keywords: 1987 Philippine Constitution; State power